Meningkatkan Hasil Belajar Siswa dengan Model Group Investigation pada Materi Zat dan Karakteristiknya - Titik Kusminarwati; Syahrin Zakiyah (Citra Dharma Cindekia, 2023)
Substances and their characteristics are learning materials that are more active in trying and experimenting, while there is a tendency for students to enjoy adventure conquering opponents in the game, which can be seen from resting activities. They often play mobile legends, or free fire. This tendency has an impact on the lack of focus of students in learning which has an effect on student learning outcomes that are not as expected. Evaluation results for 3 classes, 50% less than the passing grade. The GI (Investigation Group) model in substance and its characteristics, chosen as a fun learning model, can become a place for students' aspirations in channeling their hobby of playing gadged. GI cooperative learning model is a learning method in which students learn in groups, study groups are formed based on the topic chosen by the student. So students as the center of learning, spare the teacher more as facilitators. With reference to Kemmis and Taggard which consists of the planning, implementation, observation and reflection stages, while the instruments used are lesson plans, teacher and student observation sheets, questionnaire sheets and quiz sheets. The results of data processing and discussion of the application of the Group Investigation method in cycle I and cycle II show that individual student learning outcomes have increased as seen from the formative test scores with the number of students who score above the passing grade. Although the graph of the increase in student learning outcomes in cycle 1 and cycle 2 is not too hight, by looking at the graph of the level of motivation, it can still be concluded that the GI model can be an alternative that can be chosen for fun learning material that does a lot of experimental activities in the learning process